Patogenisitas Beberapa Isolat Cendawan Entomopatogen Metarhizium spp. terhadap Telur Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Trizelia Trizelia; My Syahrawati; Aina Mardiah (Perhimpunan Entomologi Indonesia, 2011)
Metarhizium spp. is one of the entomopathogenic fungus that can be used to control Spodoptera litura. The purpose of this research was to study the pathogenicity of Metarhizium spp. to Spodoptera litura eggs. The isolates were collected from rhizosphere of different crops i.e., cabbage, onion, leek and chili. The results showed that there was effect of all isolates on egg mortality. Mortality of S. litura eggs depend on the fungal isolates, ranged between 19.79%-75.70%. First instar larvae was also died 3 days after eclosion. The maximum mortality of first instar larvae was 58.65%. At a concentration of 108 conidia/ml, isolate Mt-kb had the highest virulence which caused higher mortality of eggs and first instar larvae.